Dalfampridine benefits ambulation but not cognition in multiple sclerosis. (January 2020) - Satchidanand, Nikhil; Drake, Allison; Smerbeck, A; Hojnacki, David; Kolb, Channa; Patrick, Kara; Weinstock-Guttman, Bianca; Motl, Robert; Benedict, Ralph HB
Background: Impaired cognition and ambulation are common in multiple sclerosis (MS). Dalfampridine is the first Food and Drug Administration (FDA)–approved medication to treat impaired ambulation in MS. Dalfampridine may benefit patients with cognitive impairment, given its effects on saltatory conduction and the association between cognitive and motor function. Objective: To examine the effects of dalfampridine on cognition in MS. To determine if the anticipated improved cognition is grounded in dalfampridine's effects on ambulation. Methods: Adults with MS were randomized to dalfampridine ( n = 45) or placebo ( n = 16) for 12 weeks. Cognition and motor function were assessed at baseline and end-point. Results: T25FW and 6-minute walk (6MW) performance improved at end-point in the treatment group but not in the placebo group ( p < 0.05). Our primary outcome, performance on the Symbol Digit Modalities Test, did not improve. About 30% ( n = 12) of the dalfampridine group demonstrated ⩾20% improved ambulation and were categorized "responders." Among "responders", Symbol Digit Modalities test performance did not improve. However, performance on the Paced Auditory Serial Addition Test improved among "responders" ( p < 0.05). Conclusion: Dalfampridine benefits timed ambulation but not cognition. Some improvement among ambulation "responders" is consistent with prior reports of cognition-motor coupling in MS (ClinicalTrials.gov #: NCT02006160).